The impact of protostellar jets on their environment - O'Connell, Barry F. (Trinity College (Dublin, Ireland). School of Physics, 2005)
The nature of the accelerated and heated gas along collimated outflows emanating from deeply embedded protostars is investigated. By analysing the shock structures and excitation conditions it is possible to deduce information concerning the flow dynamics and environmental structure governing the morphology of outflows. Narrow-band imaging at near-infrared wavelengths and various spectroscopic techniques are employed in conjunction with bow shock modeling to uncover the underlying gas dynamics and excitation structure.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin